Deskripsi Tingkat Pengetahuan Perawat tentang Perawatan Paliatif pada Pasien dengan HIV - Lutfiana Khoirotun Nisa; Indah Sri Wahyuningsih; Mohammad Arifin Noor (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Palliative care for HIV patients aims to improve the quality of life and manage the symptoms experienced. Sufficient knowledge of nurses regarding this care is essential for providing optimal care. The purpose of this study was to describe the level of knowledge of nurses about palliative care in HIV patients. This descriptive quantitative study involved nurses working in hospitals treating HIV patients. Data were obtained through a questionnaire that measured nurses' knowledge of the principles of palliative care. Data analysis was done descriptively. The results showed that out of 60 respondents, 54 people (90.0%) had good knowledge, 5 people (8.3%) had sufficient knowledge, and 1 person (1.7%) had poor knowledge.